The role of microRNAs in dexamethasone-induced skeletal muscle atrophy - Subi Ren; Jie Chai; Lijuan Zhang; JiGang Li; Xi Long; Tinghuan Zhang (Experimental Gerontology)
Muscle atrophy is characterized by a decrease in muscle mass, strength, and activity. Recently, it was determined that microRNAs (miRNAs) can regulate muscle atrophy and that dexamethasone (Dex), an allergy and autoimmune disorder treatment that can induce muscle atrophy. Therefore, this study was designed to identify miRNAs expressed in Dex-induced muscle atrophy in mice using small RNA sequencing. A total of 820 miRNAs were identified, with 58 miRNAs expressed explicitly in atrophic muscles. Dex-induced muscle atrophy miRNAs clustered separately from the differential miRNAs in aging, disuse, and cancer-induced muscle atrophy models. The target genes of Dex-induced muscle atrophy miRNAs were independently enriched in inositol phosphate metabolism, hypoxia-inducible factor-1 signaling pathway, etc. Of note, there was a significant increase in the volume of fat cells and adipose weight in the Dex group, suggesting that fat deposition during Dex-induced skeletal muscle atrophy is a unique and typical feature. Simple summary: Dexamethasone (Dex) is a glucocorticoid used to treat allergic and autoimmune diseases, but excessive use can lead to skeletal muscle atrophy. We used dexamethasone (Dex) to build a muscle atrophy model in mice, and obvious changes had taken place in mouse body weight, muscle tissue morphology and related genes. A large number of microRNAs were found to be differentially expressed, and their functions were enriched in pathways related to muscle development. At the same time, we compared the similarities and differences of microRNAs and their functions between Dex induced muscle atrophy model and other muscle atrophy models. Finally, we were surprised to find that Dex induced muscle atrophy is specifically accompanied by the accumulation of body fat.